Research on cyberspace security situation awareness - Gan-sen ZHAO; Jie-chao WU; Zi-hao CHEN; Xue-qi REN; Hao-xiang TAN; Zhao-hui MA (网络与信息安全学报)
Cyberspace is the fifth sovereignty space after the sea,land,sky and space.The security of cyberspace is closely relative to national security.How to discover threat in time,how to defense network attack,how to trace attackers were the problems to be selved.Facing the polyphyletic,isomeric,disconnected properties in the cyberspace,bases on a credible IaaS,a cyberspace security situation awareness was constructed by ontology,semantic Web and linked data theory.While guarantee the access security of integrating data,the model could make a comprehensive analysis on the properties in the cyberspace,which contributes to cyberspace governance.